2016
DOI: 10.2967/jnumed.116.176628
|View full text |Cite
|
Sign up to set email alerts
|

What We Observe In Vivo Is Not Always What We See In Vitro: Development and Validation of 11C-JNJ-42491293, A Novel Radioligand for mGluR2

Abstract: Positive allosteric modulators (PAM) of metabotropic glutamate receptor 2 (mGluR2) are a potential therapy for anxiety, schizophrenia, and addiction. Aside from pathophysiologic imaging studies, an mGluR2 PET tracer would enable confirmation of sufficient central target engagement and assist dose selection for proof-of-concept studies of PAM compounds. 11 C-JNJ-42491293, a novel high-affinity radioligand (human 50% inhibitory concentration 5 9.6 nM) for the PAM site of mGluR2, was evaluated as a selective mGlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…The radioactivity was efficiently cleared from blood (1 min/60 min ratio of 2.4) and high radioactivity in the liver, kidneys and small intestine indicated urinary and hepatobiliary excretion, as well as a possible intestinal reuptake pathway. The distribution of [ 11 C]QCA in the peripheral organs was similar to prior reports with other compounds, 51,56,69,70 in which rapid clearance of radioactivity from heart, lungs, spleen and muscle was observed. Limited brain uptake (peak value 0.42% ID/g at 1 min post injection) was observed, and thus the regional brain distribution was further studied by in vitro autoradiography.…”
Section: Resultssupporting
confidence: 87%
“…The radioactivity was efficiently cleared from blood (1 min/60 min ratio of 2.4) and high radioactivity in the liver, kidneys and small intestine indicated urinary and hepatobiliary excretion, as well as a possible intestinal reuptake pathway. The distribution of [ 11 C]QCA in the peripheral organs was similar to prior reports with other compounds, 51,56,69,70 in which rapid clearance of radioactivity from heart, lungs, spleen and muscle was observed. Limited brain uptake (peak value 0.42% ID/g at 1 min post injection) was observed, and thus the regional brain distribution was further studied by in vitro autoradiography.…”
Section: Resultssupporting
confidence: 87%
“…JNJ‐42491293 is a potent mGlu 2 PAM ( EC 50 = 7.5 nM; E max = 282%) with high affinity ( IC 50 = 9.23 nM) to the human mGlu 2 receptors . [ 11 C]JNJ‐42491293 was developed as a potential mGlu 2 PET tracer .…”
Section: Mglu Pet Tracers and Mglu Ro Measurementmentioning
confidence: 99%
“…JNJ‐42491293 is a potent mGlu 2 PAM ( EC 50 = 7.5 nM; E max = 282%) with high affinity ( IC 50 = 9.23 nM) to the human mGlu 2 receptors . [ 11 C]JNJ‐42491293 was developed as a potential mGlu 2 PET tracer . The PET data showed that [ 11 C]JNJ‐42491293 uptake reached at the plateau from 12 to 27 minutes in the rat brain after injection followed by a slow washout.…”
Section: Mglu Pet Tracers and Mglu Ro Measurementmentioning
confidence: 99%
See 2 more Smart Citations